2021
DOI: 10.33448/rsd-v10i3.11840
|View full text |Cite
|
Sign up to set email alerts
|

Organic carbon dynamics in interrows of Vitis vinifera with different years of soil use and management

Abstract: This study aimed to evaluate the effects of soil use and management on organic carbon stocks in the interrows of Vitis vinifera with different years of cultivation. A vineyard located in Rio Grande do Sul state, with 4, 9 and 16 years of management, was evaluated. Soil samples from different layers, 0.0-0.10, 0.10-0.20, 0.20-0.30, 0.30-0.40, 0.40-0.50 and 0.50-0.60 m, were collected on wheel tracks, between wheel tracks and under the planting rows. As a reference, samples were collected in native grassland of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…Several studies have investigated the effects of organic residue management on Vitis vinifera L., Malus domestica (Borkh), and Prunus persica (L.) Batsch (Frene et al., 2020; Santos et al., 2021), focusing on soil biota abundance in various soils and countries. These studies have observed a decrease in the diversity of soil organisms associated with reduced input of organic residues.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated the effects of organic residue management on Vitis vinifera L., Malus domestica (Borkh), and Prunus persica (L.) Batsch (Frene et al., 2020; Santos et al., 2021), focusing on soil biota abundance in various soils and countries. These studies have observed a decrease in the diversity of soil organisms associated with reduced input of organic residues.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanization, along with other agricultural practices, has contributed to a significant increase in crop yield and reduction in production costs over the last century. However, indiscriminate use may lead to increased density due to alterations in pore shape, which reduces permeability to water, and these indicators are the most studied to evaluate the effects of soil use and management in agricultural areas (Santos et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…al (2021) in a study of changes in soil and clay fraction after cultivation with viticulture showed that there is change in chemical attributes, mineralogy and soil fertility over the years, especially where the soil is managed for a longer time with the input of chemical fertilizers. Santos et al (2021), they concluded that soil management caused changes in soil structure and organic matter content, especially in the first 30 cm, when subjected to tractor weight in the planting line. And changing the ground cover for planting vines leads to a reduction in carbon stock, compared to native pastures, for example.…”
Section: Introductionmentioning
confidence: 99%